ANALISIS PEMBENTUKAN PORTOFOLIO OPTIMAL MENGGUNAKAN MODEL INDEKS TUNGGAL UNTUK PENGAMBILAN KEPUTUSAN INVESTASI PADA PERUSAHAAN IDX 30 BEI TAHUN 2018-2022 - Dani Adnan; Lily Setyawati Kristianti (Journal of Research and Publication Innovation, 2025)
The purpose of this research is to identify which stocks can form an efficient and optimal portfolio, determine the proportion of funds for each stock forming the optimal portfolio, and determine the expected return and risk of the optimal portfolio based on the Single Index Model. The method used in this research is descriptive research with a quantitative approach. The population used is the IDX 30 index stocks from January 2018 to December 2022, with a selected sample of 12 stocks. The research results show that out of the 12 stocks, 4 stocks are suitabel for inclusion in the optimal portfolio, namely: ADRO (42,45%), ANTM (31,81%), BBRI (16,78%), ICBP (1,72%), KLBF (5,36%), and PGAS (1,89%). This portfolio provides a return rate of 2.12% with a risk rate of 2.99%.